Early versus late stage schizophrenia. What markers make the difference?. (7th February 2019) - García-Álvarez, L.; García-Portilla, M. P.; Caso, J. R.; de la Fuente-Tomás, L.; González-Blanco, L.; Sáiz Martínez, P.; Leza, J. C.; Bobes, J.
Abstract: Objectives: To identify the psychopathological, cognitive, functional, physical health and inflammatory markers that differentiate between early-stage schizophrenia (ESSCH) and late-stage schizophrenia (LSSCH). Methods: Cross-sectional, naturalistic study of 104 patients with SCH. The sample was divided in two groups: 35 ESSCH (≤7 years' duration of illness) and 69 LSSCH (>10 years' duration of illness). Statistical analysis: chi-square test and Student's t -test and ANCOVA (or Quade test) controlling for age, sex, BMI and number of cigarettes/day. Finally, a binomial logistic regression was made. Results: ESSCH show greater negative symptom severity ( t = 2.465, p = 0.015), lower levels of IκBα ( F = 7.644, p = 0.007), were more frequently classified as normal weight (40% vs 18.8%, p = 0.032) compared with LSSCH. The binomial logistic regression model included age ( B = 0.127, p = 0.001) and IκBα ( B = 0.025, p = 0.002) and accounted for 38.9% of the variance (model df =7, chi-square =41.841, p < 0.0001). Conclusions: Age and IκBα are the unique markers that differentiate between ESSCH patients whose duration of illness is less than 7 years and LSSCH patients. These results support the hypothesis of toxicity of episodes and highlight the importance of preventing new episodes.